A pilot randomized controlled trial evaluating the impact of a skills and attitudes based program on marital quality - Alphonse Nkurunziza; Japhet Niyonsenga; Claudine Munganyinka; Jeanne Marie Ntete; Jean Mutabaruka (Discover Psychology)
Abstract Background Marital quality is influenced by numerous factors, with previous research highlighting the importance of positive attitudes and supportive practices in fostering a healthy relationship environment. However, there is a need for empirical studies that specifically examine how skills and attitudes-based practices impact marital quality. This pilot study aims to fill this gap by investigating the influence of couple skills and attitudes-based practices on marital quality, providing insights that could inform therapeutic approaches and interventions for couples seeking to improve their marital satisfaction. Methods This randomized controlled trial involved 45 married couples, aged 25–45, divided into an intervention group (23 couples) and a control group (22 couples). The intervention consisted of 8 weekly workshops designed to foster key aspects of marital quality, such as communication, expectations, and commitment. Participants in both groups were assessed using the Relationship Belief Inventory (RBI), the Marriage Expectation Scale (MES), and the Marital Commitment Questionnaire (MCQ) before and after the intervention. Results The significant main effects of time and group, as well as the time by group interaction effects for the RBI, MES, MCQ scores indicate that the intervention effectively improve dysfunctional beliefs about relationships, marital commitment, and marital expectations. The results revealed significant improvements in all three areas for the intervention group compared to the control group, highlighting the program's efficacy. Conclusion The findings suggest that targeted skills and attitudes-based practices can effectively enhance marital quality among midlife couples. By addressing both attitudes and practical skills, particularly in communication and conflict resolution, the program equips couples with essential tools to foster healthier and more resilient relationships. Future studies should examine the long-term effects of such interventions and consider larger samples for sub-Group analyses. Trial registration The Pan African Clinical Trials Registry PACTR202408536250978. Retrospectively Registered on 20 August 2024.